The Role of Celebrity Endorsement, Viral Marketing and Quality on Interest Buying - Anisa, Siti Nur; Fajri, Annisa (Economics and Business International Conference Proceeding, 2024)
This research aims to find out the influence of celebrity endorsement, viral marketing and product quality on interest in buying X products. This type of research is included in quantitative research. The population in this study is a 2020-2023 military student of the Faculty of Economics and Business of Muhammadiyah University Semarang who knows and has an interest in X products. The sampling techniques used are nonprobability samplings and purposive samplers with a sample of 95 respondents. The study uses a double linear regression analysis technique with the statistical tool SPSS version 23. The results of the research show that (1) celebrity endorsement has a significant negative impact on buying interests (2) viral marketing has an significant positive impact on purchasing interests (3) product quality has a major positive effect on purchase interests (4) celebrity endorsements, viral marketing and product quality have a significant impact simultaneously (together) on buy interests skincare x. For further research it is recommended to add or investigate different independent variables of this research in order to add variation in conducting a study.